The influence of various factors on the results of carbonation, cover depth, half-cell potential and resistivity tests that are used in the assessment of reinforcement corrosion - Akhalwaya, Mohammed Faraaz (Department of Civil Engineering, 2021)
Reinforcement corrosion is the main cause of deterioration in concrete structures. Condition assessment tests help to predict whether reinforcement corrosion is occurring and aid in the prevention of its consequences. The results of these condition assessment tests can, however, be affected by certain factors. A set of experiments that included carrying out four of these tests, namely the half-cell potential (HCP), cover depth, carbonation and resistivity tests was performed on several concrete structures on upper campus at UCT. The half-cell potential and resistivity tests were carried out across a four-month period between August and November 2018 during both dry and wet periods and on days with different temperatures. This was done to assess how changing weather conditions can affect the test results. The results from these tests were also used to do a comparison between HCP and cover depth results and HCP and resistivity results. A second set of experiments involved taking cover depth measurements and cores for carbonation testing from different locations across a building and assessing how variations in measurement location and sample size can affect the results. The HCP and resistivity results showed changes due to the effects of rain and temperature. Rainy weather caused the values to become more negative, while dry weather led to more positive values. An increase in temperature showed a slight decrease in the values of both the half-cell potential and resistivity measurements. The changes suggest that using prescribed value ranges to interpret the risk of corrosion may prove to be too simplistic. Contour plots of the HCP results proved to be a more stable method for assessing reinforcement corrosion than using prescribed value ranges. The overall trend for the comparison between HCP and cover depth results showed that HCP values decrease as cover depths decrease. The comparison between HCP and resistivity results was expected to show an overall decrease in HCP values as resistivity values decrease, but this did not hold true for some of the test locations. The results of the cover depth analysis showed significant changes in calculated statistics due to both changes in location and sample size. A cover depth analysis should thus be widespread and include a large number of measurements in order to provide useful results. The variation in results for the carbonation testing was contradictory for the two buildings that were tested, with one building showing significant variations with measurement location and the other building showing very little variation.